Unverricht-Lundborg disease in an adult female patient: a clinical case - V. A. Karlov; I. A. Zhidkova; E. Yu. Mishina; P. N. Vlasov; N. V. Margosyuk; L. P. Tingaeva; E. M. Perepelova; V. A. Perepelov; B. P. Gladov; S. A. Trukhanov (Неврология, нейропсихиатрия, психосоматика)
We have considered it appropriate to publish this case due to the rarity of progressive myoclonus epilepsy; diagnostic difficulties, particularly in the early stages of the disease (the female patient has been long followed up for diagnosed juvenile myoclonic epilepsy); the relative role of a genetic study because it has not brought results in this case, and,  finally, a problem with therapy, and a significant contribution to the  achievement of certain success of currently available antiepileptic drugs, levetiracetam in particular.